Deny and build from the actions of movements: three types of territorial autonomies in Mexico (Polis (Santiago), 2020)
What do the cases of (i) the Zapatista Army of National Liberation (EZLN), (ii) Oxchuc-Chiapas and (iii) San Andrés Totoltepec-CDMX have in common? Their processes of denial and construction that express the autonomy of their social movements in relation to the State. We present here a qualitative approach research, with bibliographic review and semi-structured interviews, carried out with the purpose of understanding the meanings and dynamics of the territorial autonomous actions of those movements in their interactions with the State. Territorial autonomy converges between the three cases, but it is expressed in different ways: (i) the construction of their own sociabilities and social and political practices that reject the totality of the State; (ii) the construction of political confrontations that reject the State form and its conditioning in life in the territory; and (iii) the construction of their own dynamics that are inserted within the State rejecting part of its dynamics.
Keywords: Autonomy; territory; social movements; State; Zapatismo; political economy